2012
DOI: 10.1111/j.1349-7006.2012.02368.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic profiles indicating genetic factors may involve in hepatocellular carcinoma familial aggregation

Abstract: Familial aggregation of hepatocellular carcinoma (HCC), the third leading cause of cancer death worldwide, has shown to be a common phenomenon. We investigated the association between the genetic background and HCC familial aggregation. Serum samples were collected from HCC family members and normal control family members for screening the differentially expressed protein peaks with the approach of surface-enhanced laser desorption ionization time-of-flight mass spectrometry. Potential genetically associated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…By integrating differential expression analysis, ChIP-seq data and PPI networks, the present results suggested that the JunB proto-oncogene (JUNB) may serve an important role in the development and progression of HCC and the immune response. In addition, apolipoprotein A2 (APOA2), which encodes a genetically susceptible protein in HCC (19), was found to exhibit the same expression pattern as JUNB. The present results may contribute to the identification of novel therapeutic targets for the treatment of HCC patients.…”
Section: Tracking the Important Role Of Junb In Hepatocellular Carcinmentioning
confidence: 99%
“…By integrating differential expression analysis, ChIP-seq data and PPI networks, the present results suggested that the JunB proto-oncogene (JUNB) may serve an important role in the development and progression of HCC and the immune response. In addition, apolipoprotein A2 (APOA2), which encodes a genetically susceptible protein in HCC (19), was found to exhibit the same expression pattern as JUNB. The present results may contribute to the identification of novel therapeutic targets for the treatment of HCC patients.…”
Section: Tracking the Important Role Of Junb In Hepatocellular Carcinmentioning
confidence: 99%
“…From this point of view, HCC can be classified by the patient's family history into familial and sporadic cases, with greater than 80% of HCC cases belonging to the latter. [13][14][15] Specifically, Shih et al performed an association analysis similar to the methods of GWAS but with a short coverage range of only 67 SNPs, of which they identified 2 associated haplotype blocks within 3 0 -phosphoadenosine 5 0 -phosphosulfate synthase 1 (PAPSS1), albeit with low significance (P7.5E-3). Individuals with a family history of HCC have an increased overall risk of developing HCC compared with those without a family history.…”
Section: Introductionmentioning
confidence: 99%
“…12 Previous familial HCC studies used methods including protein mass spectrometry, clinical and pathological characteristic association, and association analysis of a limited number of single-nucleotide polymorphisms (SNPs). [13][14][15] Specifically, Shih et al performed an association analysis similar to the methods of GWAS but with a short coverage range of only 67 SNPs, of which they identified 2 associated haplotype blocks within 3 0 -phosphoadenosine 5 0 -phosphosulfate synthase 1 (PAPSS1), albeit with low significance (P7.5E-3). 15 Therefore, to our knowledge, the specific genetic factors correlated with familial HCC have not yet been studied by GWAS, most likely due to the difficulty in collecting sufficient familial HCC cases.…”
Section: Introductionmentioning
confidence: 99%
“…Between the proteins identified in the discovery phase, there was a significant enrichment of proteins involved in the complement and coagulation activation cascades (C5, C8G, C1QC, C7, and C9), which were previously considered as biomarkers of different cancers, [17] and several apolipoproteins also reported as plasma biomarkers for different types of cancer and obesity-cancer association. [22] In contrast to these tumors, our results showed a clear decline of APOC3 associated to CRC progression, providing a significant statistical value for diagnosis. In addition, C-reactive protein (CRP), an inflammation-related protein, increased exponentially in the serum of late-stage patients.…”
Section: Discussionmentioning
confidence: 44%